PWE-070 Outcomes following local excision of benign rectal lesions—network MDT results. (28th May 2012) - Sheel, A R G; Titu, L; Skaife, P; Slawik, S; Rooney, P S
Abstract : Introduction: A regional Small and Early Rectal Cancer (SERC) MDT was established in 2008. In line with NICE guidance, all patients with stage 1 rectal cancer are referred, as well as benign lesions with a high clinical suspicion of malignancy. Historical evidence from St Mark's has shown that most rectal cancers following Local excision (LE) develop in patients with incomplete adenoma excision. We aimed to establish outcomes of LE for benign lesions in our region, focusing on adequate treatment according to histology, adequacy and type of excision. Methods: Observational study of the SERC MDT database. Results: The SERC MDT processed 137 referrals (62 f: 75 m. Median age 77 (range 36–90)). There were 79 cases with benign histology at referral. Of 74 local excision (LE) procedures, 50 were performed for ultimately benign lesions. There was one attempted LE prior to MDT referral (asterisk). The case with incomplete excision of HGD was offered classical surgery. Histopathological examination of margins was not possible in 22 cases due to piecemeal excision. All patients entered an endoscopic surveillance programme. Conclusion: The majority of the referrals to the SERC MDT are for benign lesions and we would recommend all suspicious lesions are referred in the first instance. Rates of complete excision of benign lesions can be improved. TEMS has a significantly higher complete excision rate compared to EMR. Long-term follow-up of patients with incomplete excision will be of interest. Competing interests: None declared.